A Computational Study of Fab CHK152 with CHK265 as Anti Chikungunya Virus for Rapid Test Components - Korry Novitriani; Ade Rizki Ridwan Firdaus; Bacthi Alisjahbana; Shabarni Gaffar; Muhammad Yusuf; Toto Subroto (Humanistic Network for Science and Technology (HNST), 2023)
The symptoms of chikungunya disease are generally similar to the symptoms of other viral diseases, except that chikungunya disease can cause joint disorders and even paralysis. Incorrect initial diagnosis will result in inappropriate treatment of the disease Thus it is necessary to study the identified antibodies that can neutralize and protect the body from alphavirus infections, including chikungunya. There are several antibodies that can neutralize chikungunya including CHK152 which neutralizes virus by inhibiting fusion with stabilizing the surface area of the virus, hindering the exposure of the fusion-loop, likely neutralizing infection by blocking fusion. Otherwise CHK265 inhibits the life cycle of the virus in a way neutralize infection by blocking entry at a post-attachment pre-fusion step. The low energy of binding between antigen-antibodies will stabilize the interaction of both. Therefore, this aims to find the best affinity energy for antibodies to be used in the rapid diagnostic component of anti-chikungunya virus (CHIKV). The binding energies were calculated using FireDock an efficient method for the refinement and rescoring of rigid-body docking solutions, through rearrangement of the interface sidechains and adjustment of the relative orientation of the molecules.The results of this study obtained energy scores from CKH152 and CHK265 are -125.78 and -29.94, indicate that CHK265 antibody affinity energy is higher than CHK152. It can be concluded that the best affinity energy for CHIKV diagnostic component is CHK152.Keywords: energy affinity; CHK152; CHK265; E1E2 CHIKV; molecular docking